The Description of the Contemporary Islamic Movement as Kharijites: A Critical and Analytical Study - Obalowu, Issah Abeebllah; Abdul Rahim, Adibah Binti (ADDIN, 2021)
This study aims at addressing the extent of proximity and relationship between the contemporary Islamic movements and the Kharijites. Many contemporary scholars, regardless of their motives and trends, describe modern Islamic movements as Kharijites, due to their advocacy for radical social and political reform in many of the Muslim countries. Therefore, there is a need for addressing the genuineness of this description, especially when it is generally attributed to the whole contemporary Islamic movements across the Muslim nations, as it is the case in the view of the Madkhalists. Indeed, the misplacement of this description on some Islamic movements opens the door of political oppression and leads to the justification of shedding the innocent blood and the persecution of the righteous Muslims, based on the political disagreement, as it is the case in many Arab and Muslim countries, i.e., Egypt. So, this study discusses the historical background of the contemporary Islamic movements and their relationship with the Kharijites in order to figure out the range of correspondence between the principles of Kharijites and contemporary Islamic movements. The qualitative method is being applied in the study by adopting a historical, inductive, and analytical approach. It reveals that the contemporary Islamic movements can be loosely categorized into two major groups, one of which cannot be described as the Kharijites in all perspectives, while the other one can be described as the Kharijites due to the tight closeness between their trends and ideologies and the principles of the Kharijites. Likewise, their unjustifiable and terrorist acts against innocent people permit the ascription of the name to such groups among the contemporary Islamic movements.